Dynamic Changes in Erectile Function and Histological Architecture After Intracorporal Injection of Human Placental Stem Cells in a Pelvic Neurovascular Injury Rat Model. Issue 3 (27th January 2020) - Gu, Xin; Thakker, Parth U.; Matz, Ethan L.; Terlecki, Ryan P.; Marini, Frank C.; Allickson, Julie G.; Lue, Tom F.; Lin, Guiting; Atala, Anthony; Yoo, James J.; Zhang, Yuanyuan; Jackson, John D.
Abstract: Introduction: The human placenta provides a bountiful and noncontroversial source of stem cells which have the potential for regeneration of injured tissue. These cells may restore erectile function after neurovascular tissue injury such as that seen in radical pelvic surgeries and pelvic trauma. Aim: To determine the effect of human placenta–derived stem cells on erectile function recovery and histological changes at various time points in a cavernous nerve injury rat model and to study the fate of injected stem cells throughout the regenerative process. Methods: Human placental stem cells (PSCs) were dual labeled with monomeric Katushka far red fluorescent protein (mKATE)-renLUC using a lentivirus vector. A pelvic neurovascular injury–induced erectile dysfunction model was established in male, athymic rats by crushing the cavernous nerves and ligating the internal pudendal neurovascular bundles, bilaterally. At the time of defect creation, nonlabeled PSCs were injected into the corpus cavernosum at a concentration of 2.5 × 10 6 cells/0.2 mL. The phosphate-buffered saline–treated group served as the negative control group, and age-matched rats (age-matched controls) were used as the control group. Erectile function, histomorphological analyses, and Western blot were assessed at 1, 6, and 12 weeks after model creation. The distribution of implanted, dual-labeled PSCs was monitored using an in vivo imaging system (IVIS). Implanted cells were further tracked by detection of mKATE fluorescence in histological sections. Main Outcome Measure: The main outcome measure includes intracavernous pressure/mean arterial pressure ratio, neural, endothelial, smooth muscle cell regeneration, mKATE fluorescence, and IVIS imaging. Results: The ratio of intracavernous pressure to mean arterial pressure significantly increased in PSC-injected rats compared with phosphate-buffered saline controls ( P < 0.05) at the 6- and 12-week time points, reaching 72% and 68% of the age-matched control group, respectively. Immunofluorescence staining and Western blot analysis showed significant increases in markers of neurons (84.3%), endothelial cells (70.2%), and smooth muscle cells (70.3%) by 6 weeks in treatment groups compared with negative controls. These results were maintained through 12 weeks. IVIS analysis showed luminescence of implanted PSCs in the injected corpora immediately after injection and migration of cells to the sites of injury, including the incision site and periprostatic vasculature by day 1. mKATE fluorescence data revealed the presence of PSCs in the penile corpora and major pelvic ganglion at 1 and 3 days postoperatively. At 7 days, immunofluorescence of penile PSCs had disappeared and was diminished in the major pelvic ganglion. Clinical Implications: Placenta-derived stem cells may represent a future "off-the-shelf" treatment to mitigate against development of erectile dysfunction after radical prostatectomy or other forms of pelvic injury. Strength & Limitations: Single dose injection of PSCs after injury resulted in maximal functional recovery and tissue regeneration at 6 weeks, and the results were maintained through 12 weeks. Strategies to optimize adult stem cell therapy might achieve more effective outcomes for human clinical trials. Conclusion: Human PSC therapy effectively restores the erectile tissue and function in this animal model. Thus, PSC therapy may provide an attractive modality to lessen the incidence of erectile dysfunction after pelvic neurovascular injury. Further improvement in tissue regeneration and functional recovery may be possible using multiple injections or systemic introduction of stem cells.